Assessing Moderate to Vigorous Physical Activity in Older Adults: Validity of a Commercial Activity Tracker - Briggs, Brandon C.; Hall, Katherine S.; Jain, Chani; Macrea, Madalina; Morey, Miriam C.; Oursler, Krisann K. (Frontiers in Sports and Active Living, 2022)
Purpose: Despite the potential for commercial activity devices to promote moderate to vigorous physical activity (MVPA), limited information is available in older adults, a high-priority target population with unique gait dynamics and energy expenditure. The study purpose was to investigate the content validity of the Garmin Vivosmart HR device for step counts and MVPA in adults ≥65 years of age in free-living conditions. Methods: Thirty-five participants (M age= 73.7 (6.3) years) wore Garmin and ActiGraph GT3X+ devices for a minimum of 2 days. Accuracy and intra-person reliability were tested against a hip worn ActiGraph device. Separate analyses were conducted using different accelerometer cut-off values to define MVPA, a population-based threshold (≥2,020 counts/minute) and a recommended threshold for older adults (≥1,013 counts/minute). Results: Overall, the Garmin device overestimated MVPA compared with the hip-worn ActiGraph. However, the difference was small using the lower, age-specific, MVPA cut-off value (median (IQR) daily minutes; 50(85) vs. 32(49), p=0.35) in contrast to the normative standard (50(85) vs. 7(24), p<0.001). Regardless of the MVPA cut-off, intraclass correlation showed poor reliability (ICC (95% CI); 0.16(-0.40, 0.55) to 0.35(-0.32, 0.7)) which was supported by Bland-Altman plots. Garmin step count was both accurate (M step difference: 178.0, p=0.22) and reliable (ICC (95% CI; 0.94) (0.88, 0.97)). Conclusion: Results support the accuracy of a commercial activity device to measure MVPA in older adults but further research in diverse patient populations is needed to determine clinical utility and reliability over time.